(untitled) (Revista de Ciências Agroveterinárias, 2008)
The search for clean foods is growing around the world and tomato is one of the most demanded vegetables. However, it is difficult to grow tomato using organic systems due to the large number of insects and diseases that attack the plant. This work aimed to evaluate the organic tomato production in different crop environments. Six treatments were tested: greenhouse with afídeo insect-proof screens (0,5mm); with citros insect-proof screens (1,0mm); with clarite insect-proof screens (2,0mm); without insect-proof screens; greenhouse structure without polyethylene covered with citros insect-proof screens in the upper and borders parts; cultivation in field. Fruit production, plant development, insect and disease incidence were assessed. The greenhouse provided higher fruit production, better plant development and lower Late Blight (Phythophtora infestans) incidence. The use of insect-proof screens on the sidewall of greenhouse is effective to reduce worm attacks to the fruit without reducing tomatoes production.